Cytotoxicity and Antiangiogenic Activity of Turbinaria ornata Agardh and Padina australis Hauck Ethanolic Extracts - Jenefa L. Canoy; Jayzon G. Bitacura (Analytical Cellular Pathology)
Brown macroalgae species are constantly reported as potential sources of bioactive compounds useful in inhibiting cell proliferation and vascular formation. Thus, this study was conducted to determine and compare the in vitro cytotoxic activities of Turbinaria ornata Agardh and Padina australis Hauck ethanolic extracts against baker’s yeast (Saccharomyces cerevisiae) using the resazurin reduction test (RRT) and investigate their in vivo antiangiogenic activity through duck (Anas platyrhynchos) chorioallantoic membrane (CAM) assay. Both T. ornata and P. australis ethanolic extracts exhibited cytotoxic activities at IC50 of 530.53 ppm and 528.78 ppm, respectively, and significant cytotoxicity was determined in 750 ppm and 1000 ppm concentrations of T. ornata and 1000 ppm concentration of P. australis. Also, both T. ornata and P. australis ethanolic extracts exhibited antiangiogenic activity (100% vascular inhibition) as all the concentrations of both species caused severe vascular damage in all the duck CAM samples treated. These results show the potential future application of these species for cytotoxic activities and vascular inhibition. The conduct of further tests using other model systems is recommended.